RESPONSE OF FORAGE SORGHUM TO WATER AVAILABILITY IN A TYPIC QUARTZIPSAMMENT - Andrade Júnior, Ildeu de Oliveira (2019)
The objective of this work was to determine the factors of soil water availability (FSWA) that result in the highest agronomic performance of irrigated forage sorghum, with no changes in the plants' chemical-bromatological composition. The experiment was conducted at the Montes Claros State University, Janaúba campus, MG, Brazil, in a Typic Quartzipsamment (Neossolo Flúvico Psamítico - Embrapa) with 59 mm of soil water storage capacity in the 0.0-0.3 m layer, under drip irrigation. A randomized block design with four replications and a split-plot arrangement was used, consisting of five FSWA (f0.2 = 0.20; f0.35 = 0.35; f0.5 = 0.50; f0.65 = 0.65, and f0.8 = 0.80) in the plots and two simple forage sorghum hybrids (Volumax® and BRS-655) in the split-plots. The evaluations were based on fortnightly measurements of plant height, plant transversal diameter, number of leaves per plant, leaf area index, relative chlorophyll content, stem diameter, panicle length, dry matter yield, water use efficiency, crude protein, mineral matter, acid detergent fiber, neutral detergent fiber, and lignin. The FSWA of 0.20 and 0.35 increased dry matter yield and plant height of the two evaluated sorghum hybrids. The Volumax hybrid presented more crude protein content and acid detergent fiber. The evaluated FSWA did not change the chemical-bromatological composition of the sorghum hybrids.